Risk of cardiovascular events in patients with metabolic syndrome: Results of a population-based prospective cohort study (PURE Turkey) - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2020)
Objective: Metabolic syndrome (MetS) includes several cardiovascular (CV) risk factors. This study aimed to assess CV risk of MetS, contribution of its components to the risk, and whether MetS provides additional risk beyond its components. Methods: The Prospective Urban Rural Epidemiology (PURE) Turkey cohort included 3933 individuals aged between 35 and 70 years, with a median follow-up of 8.9 years. MetS was diagnosed as the presence of any of the following criteria: high blood pressure, high fasting plasma glucose, abdominal obesity, low HDL-cholesterol, or high triglycerides. The primary outcome was the composite of fatal CV events, non-fatal myocardial infarction, stroke or heart failure, adjusted for age, sex, smoking, family history of CV diseases, and LDL-cholesterol. Results: The primary outcome was more common in the MetS group [178 (9.2%) vs. 70 (3.5%); corresponding incidence rate of 11.3 vs. 4.2 per 1000 person-years; log-rank p<0.001]. Each component was significantly associated with the primary outcome; however, when the components were sequentially included in the model, abdominal obesity and high triglycerides did not provide additional risk on top of the other three components. The hazard ratio for MetS for the primary outcome was 2.12 (95% confidence interval 1.59-2.81, p<0.001), and the discriminative ability (c-statistics) of the models with MetS and the components was similar. Conclusion: MetS increases the risk of CV events more than two-fold. High blood pressure, high fasting plasma glucose, and low HDL-cholesterol are the top three components of MetS for CV risk. MetS and its components have a similar discriminative ability for CV events.
Keywords: metabolic syndrome; cardiovascular diseases; mortality; cohort study; CORONARY-HEART-DISEASE; CHOLESTEROL EDUCATION-PROGRAM; RURAL EPIDEMIOLOGY PURE; DIABETES-MELLITUS; MORTALITY; PREVALENCE; VALIDATION; IMPACT